2017
DOI: 10.1021/acs.est.7b03369
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Expression of Pteris vittata Arsenite Antiporter PvACR3;1 Reduces Arsenic Accumulation in Plant Shoots

Abstract: Arsenic (As) is a toxic carcinogen so it is crucial to decrease As accumulation in crops to reduce its risk to human health. Arsenite (AsIII) antiporter ACR3 protein is critical for As metabolism in organisms, but it is lost in flowering plants. Here, a novel ACR3 gene from As-hyperaccumulator Pteris vittata, PvACR3;1, was cloned and expressed in Saccharomyces cerevisiae (yeast), Arabidopsis thaliana (model plant), and Nicotiana tabacum (tobacco). Yeast experiments showed that PvACR3;1 functioned as an AsIII-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…The results observed by them in yeast indicated that PvACR3; 1 is a well developed antiporter that efflux As into the medium. Moreover, they also found that Arabidopsis thaliana and Nicotiana tabacum accumulated higher levels of As and reduced their accumulation in shoots 75 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results observed by them in yeast indicated that PvACR3; 1 is a well developed antiporter that efflux As into the medium. Moreover, they also found that Arabidopsis thaliana and Nicotiana tabacum accumulated higher levels of As and reduced their accumulation in shoots 75 .…”
Section: Discussionmentioning
confidence: 97%
“…A study conducted by Chen et al . showed that cloning of As- antiporter ACR3 Pteris vittata , PvACR3; 1 was done and expressed in Arabidopsis thaliana and Nicotiana tabacum and yeast 75 . The results observed by them in yeast indicated that PvACR3; 1 is a well developed antiporter that efflux As into the medium.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies show that overexpression of PvACR3 in Arabidopsis greatly increased As(III) translocation from roots to shoots, suggesting that PvACR3 functions as a plasma membrane efflux transporter involved in the xylem loading of As(III) (Wang et al, 2018). Different from PvACR3, PvACR3;1 was localized to the vacuolar membrane when the gene was heterologously expressed in Arabidopsis and tobacco (Chen, Hua et al, 2017). Also, contrary to PvACR3, expressing PvACR3;1 in Arabidopsis and rice greatly decreased As(III) translocation from roots to shoots, probably by sequestering As(III) into the vacuoles (Chen, Hua et al, 2017;Chen, Hua et al, 2019).…”
Section: Arsenic Transporters In As Hyperaccumulator Pteris Vittatamentioning
confidence: 99%
“…Furthermore, disruption of inositol transporters (AtINT2 and AtINT4) can decrease As concentrations in phloem and subsequently decrease As content in leaves [120]. Also, As(III) antiporter PvACR3;1 mediated in it sequestration into vacuoles increasing As concentrations in roots (14-29%) and decreasing its content in shoots (55-61%) [121]. Knockout of OsABCC1 transporter (ATP-binding cassette, ABC) can limit As transport and accumulation in the shoots [122].…”
Section: As Concentrations In Soil/fly Ash/plantmentioning
confidence: 99%